Optical determination of temperature and concentrations of homogeneous turbulent gas mixtures. (January 2017) - Ren, Tao; Modest, Michael F.
Highlights: An inverse calculation model is developed for homogeneous turbulent gaseous mixture. Mean temperature, concentration and the rms values are retrieved for mixture of CO2, H2 O and CO. Optimal spectral ranges for retrieving turbulent scalars of the gas mixtures are discussed. Abstract: In this study, a previously developed inverse radiation model for a single gas species is extended to mixtures of the combustion gas species CO2, H2 O and CO. Time-averaged transmissivities and their root-mean-square (rms) values are successfully related to time-averaged temperatures, species concentrations and their rms values by considering interactions between turbulence and radiation (TRI). The sensitivity of the rms transmissivity spectra to all the parameters to be retrieved are examined and optimal wavenumber ranges for retrieving turbulent scalars of the gas mixtures are discussed. To validate the models, measured spectra are synthesized for different combinations of species concentrations, temperatures, turbulent intensities, pressure path length and turbulent length scales. Results show that mean and rms temperature and species concentrations and other turbulent scalars can be retrieved accurately from turbulent transmissivity measurements as long as the turbulent intensity is below 15% and the pressure path length for the gas mixture is less than 60 bar · cm.